Design and analysis of a mobile robot with novel caster mechanism for high step-overcoming capability - Woojae Lee; Jeongeun Kim; Taewon Seo (Scientific Reports)
Abstract The mobile robot market is experiencing rapid growth, playing a pivotal role in various human-centric environments like restaurants, offices, hotels, hospitals, apartments, and factories. However, current differential-driven mobile robots, employing conventional casters and wheel motors, encounter limitations in surmounting uneven surfaces and high steps due to constraints caused by wheel and caster dimensions. While some robots address these challenges by incorporating optimized wheel shapes and additional motors, this invariably leads to an increase in both size and cost. This research introduces an innovative solution; a novel caster-wheel mechanism designed to enhance the high-step overcoming capability of mobile robots without necessitating alterations to their overall size and structure. By incorporating a sub-wheel linked to a passive joint, the driving force is effeciently converted into a vertical force, thereby empowering the mobile robot to navigate obstacles 85% larger than its caster-wheel radius. Crucially, this innovative caster can be seamlessly manufactured and integrated, offering the potential for widespread adoption as a replacement for conventional casters. Validation through comprehensive simulations and experiments conducted on a prototype robot has been presented in this article, demonstrating its effectiveness even at a robot velocity of 0.1 m/s. This pioneering solution holds significant promise for diverse applications across various mobile robot configurations, presenting a compelling avenue for further exploration and implementation in the field.